The Relationship Between Transparency, Accountability, and Participatory Management of Village Funds on Community Welfare in the Lintong Nihuta Sub-District, Humbang Hasundutan District - Harahap, Misna Doharni; Syafii, M. (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study aims to determine how much the relationship between transparent, accountable, and participatory management of village funds on community welfare in Lintong Nihuta District, Humbang Hasundutan Regency. The type of research used is quantitative. The population used in this study were village officials and community residents totaling 33,412 people. The sample was selected using the Nonprobability sampling method and calculated using the Slovin formula, which amounted to 100 people. This research data was obtained from observation, documentation, and distributing research questionnaires to respondents. The results showed that Transparent and Participatory variables had a positive and significant effect on Community Welfare, but Accountable had a positive and insignificant effect on community welfare.